2023
DOI: 10.1039/d3ra03869f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long chain fatty acids on the memory switching behavior of tetraindolyl derivatives

Surajit Sarkar,
Hritinava Banik,
Farhana Yasmin Rahman
et al.

Abstract: Dynamic transition of resistive memory behaviour from volatile threshold switching to non-volatile WORM memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“… , However, for real practical applications, data retention time needs to be increased further. It has been observed that by modifying the device fabrication like insertion of nanomaterials and other external agents, it is possible to enhance the data retention time. , An in-depth study is going on in our laboratory in this direction.…”
Section: Resultsmentioning
confidence: 99%
“… , However, for real practical applications, data retention time needs to be increased further. It has been observed that by modifying the device fabrication like insertion of nanomaterials and other external agents, it is possible to enhance the data retention time. , An in-depth study is going on in our laboratory in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…has been found to increase the memory performance. 3,20,21 In general, resistive switching memory devices utilize two or more stable resistance states of the active layer to store binary or multibit data. 21 For a device with two stable resistance states, one of them can be regarded as binary '0' and the other as binary '1'.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 For a device with two stable resistance states, one of them can be regarded as binary '0' and the other as binary '1'. 3 The states can be interchanged upon application of suitable bias voltage corresponding to the SET and RESET operations. 12 In some cases, the OFF state of the device cannot be retrieved once it is SET to the ON state even after the application of an external electric field.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations